Conditions of the formation and filtration-capacitive properties of the lower cretaceous deposits of the Tavdinsk mega outshot in the Iussk oil and gas bearing region - E. O. Dernova; E. A. Kapranova; J. V. Shcherbina (Известия высших учебных заведений: Геология и разведка)
In the presented work, the differences of mechanisms of the formation of the Lower Gotterivian deposits are considered based on the results of lithological-petrophysical studies of core samples on 5 wells of Leushin’s (approx. 150 samples) and Vikulov’s (approx. 150 samples) assises. The area covered by the studies is located on the border of the Khanty-Mansi Autonomous Okrug and Sverdlovsk region. The differences in the mechanisms of the formation of the Vikulov’s and Leushin’s assises with the use of core macrodescription data, biofacies, granulometric, petrographic and X-ray structure analyses are considered and compared. The Lower Cretaceous deposits of the studied area are represented by alternating aleurolites and argillites with rare interbeds of sandstones. The granulometrical factors most commonly used for the interpretation of sedimentation environments, the median grain size (Md), the average grain size (Xcp), the sort factor (S0), the asymmetry factor (As) and the excesses (Ex), reflecting the main characteristics of the grains distribution, are considered. According to the granulometric analysis, bar graphs of the distribution of mass fractions in percent by fractions were built and analysed. For genetic interpretation, the CM Passega diagram, construction of which is based on the mechanism of particle transfer and directly depends on the flow dynamics, was used. Conclusions about the conditions of the deposits formation are made. The reservoir properties of detrital rocks are often influenced by many of the factors discussed above: the median grain size, sorting of the detrital part, composition, amount and type of cement, compaction processes, recrystallisation, bore-hole mining and authigenic mineral formation. Based on the studies carried out, the influence of various factors on reservoir properties was analysed.